Band-structure simulations for overlap wave functions between electrons and holes for recombination in undoped GaAs/AlGaAs heterostructures - Kim, Do Hoon; Lee, Jae Hyun; Son, Seok Kyun (Journal of the Korean Physical Society, 2022)
Here, we studied the spatial separation between the electrons and holes in the undoped GaAs/AlGaAs heterostructures to optimize overlap wave functions for recombination. We describe the band-bending situation for introducing electrons and holes in an undoped GaAs quantum well: four different undoped GaAs/AlGaAs heterostructure designs are simulated using a 1D-Poisson and Schrödinger equations self-consistently to determine the most appropriate design of GaAs/AlGaAs heterostructures for higher effective single-photon emission. According to our result, we can demonstrate that a small overlap can be expected between electron and hole wave functions with 60 nm GaAs quantum well, leading to a significant (non-zero) probability of photon emission by suitable recombination. In addition, we can expect that even narrower wells would be better still up to 30 nm for less spatial separation along the growth axis of the induced device between electrons and holes. By adjusting the back-barrier position (so varying the GaAs quantum well depth), we suggested an appropriate calculation approach toward building fully dopant free GaAs/AlGaAs heterostructures for single-photon emission.
Keywords: GaAs/AlGaAs heterostructures; Photon emission; Two-dimensional electron gas; Two-dimensional hole gas